Dampak Pengakuan dan Pajak Terutang PPh Pasal 23 terhadap Penghasilan Neto: Perusahaan Manufaktur yang Tercatat di Bursa Efek Indonesia - Misheleiloen, Misheleiloen; Widantia, Kemuning Ananta (Lembaga Penelitian Universitas YARSI, 2025)
The purpose of this study is to determine whether the simultaneous effect of Income Tax Article 23 and tax payable on net profit, to determine whether the recognition of Income Tax Article 23 carried out by manufacturing companies affects the amount of net profit and to determine whether the tax payable carried out by manufacturing companies affects the amount of net profit. This type of research is a quantitative research type. The type of data used in this study is secondary data in the form of financial statements of companies, such as the company's profit and loss report and its Income Tax. The population in this study was listed for all manufacturing companies in the company report. The findings of Income Tax Article 23 affect net profit in manufacturing sector companies. It can be concluded that Hypothesis 1 which states that there is an influence between Income Tax Article 23 on Net Profit. It can be concluded that Hypothesis 2, which states that there is an influence between tax payable and net profit is accepted. Managerial Implications Financial managers in manufacturing companies need to improve efficiency in tax planning, especially to manage Article 23 Income Tax and tax payable optimally.